The Effect of Work Ethos on Employee Performance at PT. Pos Indonesia Pamulang Branch - Ika Ayu Mardianingrum; Imas Masriah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of work ethic on employee performance at PT. Pos Indonesia Pamulang Branch. The method used is explanatory research with a sample of 50 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this research variable work ethic obtained an average score of 3.784 with good criteria. Employee performance variable obtained an average score of 3.852 with good criteria. Work ethic has a positive and significant effect on employee performance with the regression equation Y = 12,242 + 0.694X, and the correlation coefficient value of 0.800 or has a strong relationship level with a determination value of 64.1%. Hypothesis test obtained sig. 0.000 < 0.05.